Effects of Child Marriage on Girls’ Education and Empowerment - Shamnaz Arifin Mim (Intelektual Pustaka Media Utama, 2017)
Although Convention on the Rights of Child declared that any marriage of an under 18 child will be considered as “Child Marriage”, the age limit of girls’ marriage was proposed to change from 18 to 16 in the draft Child Marriage Restraint Act Bangladesh 2014. This paper aims to analyse the effects of child marriage on Bangladeshi village girls’ formal education and empowerment which hopefully will lead to bring awareness among the patriarchal societies. Rangpur region was purposively selected to design this study in a case study approach. The concept of empowerment was used with an interpretive methodological approach which allowed to consciously interpreting the data from secondary relevant sources. The findings of this review article revealed the ways in which child marriages hinder the opportunity of girls to be educated and push them back to not being empowered in the patriarchal society. The study’s implication for policy and practice rooted deeply on the collaboration of NGO programmes, government interventions and family support.